Preoperative and perioperative use of levosimendan in cardiac surgery: European expert opinion. (1st April 2015) - Toller, W.; Heringlake, M.; Guarracino, F.; Algotsson, L.; Alvarez, J.; Argyriadou, H.; Ben-Gal, T.; Černý, V.; Cholley, B.; Eremenko, A.; Guerrero-Orriach, J.L.; Järvelä, K.; et al.
Abstract: In cardiac surgery, postoperative low cardiac output has been shown to correlate with increased rates of organ failure and mortality. Catecholamines have been the standard therapy for many years, although they carry substantial risk for adverse cardiac and systemic effects, and have been reported to be associated with increased mortality. On the other hand, the calcium sensitiser and potassium channel opener levosimendan has been shown to improve cardiac function with no imbalance in oxygen consumption, and to have protective effects in other organs. Numerous clinical trials have indicated favourable cardiac and non-cardiac effects of preoperative and perioperative administration of levosimendan. A panel of 27 experts from 18 countries has now reviewed the literature on the use of levosimendan in on-pump and off-pump coronary artery bypass grafting and in heart valve surgery. This panel discussed the published evidence in these various settings, and agreed to vote on a set of questions related to the cardioprotective effects of levosimendan when administered preoperatively, with the purpose of reaching a consensus on which patients could benefit from the preoperative use of levosimendan and in which kind of procedures, and at which doses and timing should levosimendan be administered. Here, we present a systematic review of the literature to report on the completed and ongoing studies on levosimendan, including the newly commenced LEVO-CTS phase III study (NCT02025621 ), and on the consensus reached on the recommendations proposed for the use of preoperative levosimendan. Highlights: Review of cardiac and non-cardiac effects of intraoperative levosimendan treatment A consensus on the use of levosimendan in the pre-operative settings is presented. Clear recommendations are proposed. The ongoing studies on intraoperative levosimendan are described and commented.